Mercury Deposition in South China Across the Ordovician‐Silurian Transition: Implications for Climate Change - Weiliang Kong; Zhen Qiu; Jiaqiang Zhang; Wen Liu; Qin Zhang (Geochemistry, Geophysics, Geosystems)
Abstract Most of the global climate changes are closely associated with volcanic activity. However, the link between global cooling during the Ordovician‐Silurian (O‐S) transition and volcanism remains unclear due to limited constraints on large volcanic events before, during, and after the peak of the Hirnantian glaciation (PHG). Here, we present high‐resolution mercury (Hg) concentrations and isotopes from South China across the O‐S transition to assess volcanic activity and its contributions to climate changes. Anomalous Hg enrichments and volcanic‐range Hg isotopes in samples above volcanic ash layers confirm the effectiveness of Hg as a tracer of volcanic events. Variations in Hg isotopes across the O‐S transition reveal multiple Hg sources related to volcanic activity, that is, dominant volcanic Hg input during pre‐PHG and post‐PHG‐2, deposition of volcanic‐sourced atmospheric Hg(II) to seawater during PHG, and increased terrestrial Hg input from enhanced weathering during post‐PHG‐1. We propose that prolonged global cooling was driven by an albedo catastrophe caused by volcanic aerosols and sustained by reduced atmospheric CO2 levels due to enhanced organic carbon burial and weathering. This study highlights Hg as a tracer of volcanic activity and provides new evidence on the role of volcanism in driving climate changes across the O‐S transition.